2018
DOI: 10.1007/s10668-018-0203-2
|View full text |Cite
|
Sign up to set email alerts
|

How farmers’ characteristics influence spontaneous spreading of stone bunds in the highlands of Ethiopia: a case study in the Girar Jarso woreda

Abstract: This study aims to identify key differences between farmers who spontaneously implement stone bunds (i.e. farmers implementing stone bunds by their own initiative) and farmers who do not. Data were collected in the Girar Jarso woreda in the central highlands of Ethiopia, through a household survey with 80 farmers: 40 with spontaneously implemented stone bunds and 40 without. Independent samples t test, principal component analysis and regression analysis were used to analyse the data. Results show that five ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…Moreover, compared with the NSF, SF are farmers with better knowledge as well as experience in IFM. This was also observed in a previous study that showed that spontaneously implemented stone bunds were more integrated with compost and manure use to produce high yields and sufficient crop residues for livestock feeds (Abi et al, 2018b). Results also indicate that SF have a better farm planning and more positive future prospects to change and to make improvements in their household food security and living condition, and therefore have a longer planning horizon than the NSF.…”
Section: Farmer Socio-cultural Characteristicssupporting
confidence: 80%
See 4 more Smart Citations
“…Moreover, compared with the NSF, SF are farmers with better knowledge as well as experience in IFM. This was also observed in a previous study that showed that spontaneously implemented stone bunds were more integrated with compost and manure use to produce high yields and sufficient crop residues for livestock feeds (Abi et al, 2018b). Results also indicate that SF have a better farm planning and more positive future prospects to change and to make improvements in their household food security and living condition, and therefore have a longer planning horizon than the NSF.…”
Section: Farmer Socio-cultural Characteristicssupporting
confidence: 80%
“…Work motivation is directly related to the perception that farmers have on implemented stone bunds. Results also show that SF have a more positive perception of stone bunds than the NSF, which is of course due to the experienced positive effects of stone bunds on soil erosion, soil productivity and crop yields (Abi et al, 2018b). Not surprisingly, results also show that SF have a better sense of ownership and responsibility to protect and maintain implemented stone bunds than NSF.…”
Section: Farmer Socio-cultural Characteristicsmentioning
confidence: 74%
See 3 more Smart Citations